2018
DOI: 10.1016/j.tvjl.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Enteric coronavirus infection in adult horses

Abstract: A new enteric virus of adult horses, equine coronavirus (ECoV), has recently been recognized. It is associated with fever, lethargy, anorexia, and less frequently, colic and diarrhea. This enteric virus is transmitted via the feco-oral route and horses become infected by ingesting fecally contaminated feed and water. Various outbreaks have been reported since 2010 from Japan, Europe and the USA. While the clinical signs are fairly non-specific, lymphopenia and neutropenia are often seen. Specific diagnosis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 32 publications
(62 reference statements)
6
77
1
12
Order By: Relevance
“…A recent seroprevalence study showed an increased proportion of ECoV infection in draft horses (17.6%), which was not apparent in the current study and likely reflects a difference in populations (Kooijman et al, 2017). Similar to other studies, ECoV infection rates were increased in the cooler months of the year, with peak prevalences in January through March likely related to husbandry changes and possible decreased viability of the virus in hot, dry temperatures (Kooijman et al, 2017;Pusterla et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A recent seroprevalence study showed an increased proportion of ECoV infection in draft horses (17.6%), which was not apparent in the current study and likely reflects a difference in populations (Kooijman et al, 2017). Similar to other studies, ECoV infection rates were increased in the cooler months of the year, with peak prevalences in January through March likely related to husbandry changes and possible decreased viability of the virus in hot, dry temperatures (Kooijman et al, 2017;Pusterla et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Equine coronavirus (ECoV) is recognised as a cause of fever, anorexia, lethargy, leukopenia, and gastrointestinal disease in adult horses . Disease outbreaks have been reported in adult horses in boarding stables or competitive facilities across the United States, Europe, and Japan (Oue et al, 2013;Pusterla et al, 2013;Miszczak et al, 2014;Pusterla et al, 2018). The recent increase in positive cases likely reflects increased awareness of the virus, and increased availability and timeliness of testing through fecal real-time quantitative polymerase chain reaction (qPCR) (Pusterla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The breeds of the affected horses reflect those breeds seen at the WSU-VTH [14]. While most reports for this infection occur during winter [3], 3 of 5 horses in our study were admitted during the spring-summer. This is not surprising and reflects the sporadic nature of this infection [14].…”
Section: Discussionsupporting
confidence: 49%
“…The most common clinical signs observed in our study included anorexia, lethargy, and fever, all characteristic of this infection [2,3]. Changes in manure consistency (diarrhea and soft feces) were observed in all of the positive horses; interestingly, this is higher than previously reported [2e4,6].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation